The Multi-Field-Coupled Model and Optimization of Absorbing Material's Position and Size of Electronic Equipments. (20th July 2010) - Duan, B. Y.; Qiao, H.; Zeng, L. Z.
Abstract : There are three fields in electronic equipment such as structure deformation (S), temperature (T), and electromagnetic (EM) fields. Both deformation and temperature will affect the electromagnetic shielding performance of the equipment considerably, particularly in the case of enclosure with small volume and high packaging density. Because the position of electronic device and the shape of outlet will be changed with structural deformation, there must be therefore an adherent relationship among three fields. To begin with, this paper presents a three-field-coupled model called STEM. Then, to enhance the capability of electromagnetic shielding of the equipment, an efficient way is to attach absorbing material to the inside of it. Under the condition of pregiven material characteristics itself, the position and size of absorbing material are of significant effort on electromagnetic shielding. The optimization model based on STEM is developed in this paper. Next, the numerical and practical experiments of an actual enclosure are given to demonstrate the feasibility and validity of the model and methodology.